Perfil biosicosocial de la persona ostomizada que acude a medicáncer, Medellín 1995 - Múnera Garcés, Adela María; Ospina de González, Bernarda; Ramírez Restrepo, Dora Lucía; Jaramillo Londoño, Eugenia; Londoño Echeverri, Jaime (Investigación y Educación en Enfermería, 2013)
.